Dimerization of SARS-CoV-2 3CLpro and the Role of the A7G/V125G Zipper Interface - Rafida, Razali; Cahyo, Budiman; Vijay, Kumar (Bentham Science Publishers, 2026)
Introduction/Objectives: The 3-chymotrypsin-like protease (3CLpro) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is essential for viral replication and is catalytically active only in its dimeric form. Elucidating the molecular determinants that stabilize this dimer may uncover novel antiviral drug targets. This study aimed to characterize the oligomerization behavior of wild-type 3CLpro and to elucidate the functional role of an alanine– valine zipper motif in dimer stability and enzymatic activity. Methods: Wild-type 3CLpro (3CLpro-WT) was heterologously expressed in Escherichia coli BL21(DE3) and purified by nickel-affinity chromatography. Oligomerization behavior was examined using Size-Exclusion Chromatography (SEC) under varying protein concentrations, pH conditions, and ionic strengths. An alanine–valine zipper mutant (A7G/V125G; 3CLpro-ZM) was generated by site-directed mutagenesis, overexpressed, purified using the same protocol, and analyzed for changes in folding, oligomerization, and enzymatic activity. Results: 3CLpro-WT predominantly existed as a stable dimer, independent of protein concentration and ionic strength, but was destabilized under extreme pH conditions. In contrast, 3CLpro-ZM exhibited a perturbed dimerization equilibrium, altered secondary structure, and a pronounced reduction in both protease and esterase activities compared with the wild-type enzyme. Discussion: These findings demonstrate that hydrophobic interactions are the primary force stabilizing the 3CLpro dimer, while ionic interactions provide pH-sensitive modulation. Disruption of the alanine–valine zipper compromises dimer integrity and allosterically impairs catalytic activity, despite the mutation being distant from the active site. Conclusion: The Ala7–Val125 interface contributes to 3CLpro stability and activity and may be a promising site for future allosteric inhibitor design.